Perioperative anesthetic management of a pregnant mother with placenta percreta - Roshana Prasad Mallawaarachchi; Ramani Pallemulla (Wolters Kluwer Medknow Publications, 2018)
Placenta percreta is a rare condition during pregnancy in which the abnormal presentation of placenta penetrates the uterine wall and invades into the surrounding organs including bowel and bladder. With the increasing rate of cesarean sections, the incidence of placenta percreta has also increased. This is a condition which gives rise to a major obstetric hemorrhage, peripartum hysterectomy, and maternal and fetal morbidity and mortality. This case report presents a successful obstetric and anesthetic management of a patient with preoperatively diagnosed placenta percreta.